2019
DOI: 10.1021/acs.nanolett.9b04445
|View full text |Cite
|
Sign up to set email alerts
|

Collective Force Generation by Molecular Motors Is Determined by Strain-Induced Unbinding

Abstract: In the living cell, we encounter a large variety of motile processes such as organelle transport and cytoskeleton remodeling. These processes are driven by motor proteins that generate force by transducing chemical free energy into mechanical work. In many cases, the molecular motors work in teams to collectively generate larger forces. Recent optical trapping experiments on small teams of cytoskeletal motors indicated that the collectively generated force increases with the size of the motor team but that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…Within the cell, the condensation force we identified will compete with forces exerted by molecular motors. We showed that actin transport by growing microtubule plus-ends results in much lower forces (0.10 pN) than are measured for microtubule motor proteins (1 pN to 10 pN) [39,40]. In direct competition, motor forces would therefore likely dominate over the condensation forces.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Within the cell, the condensation force we identified will compete with forces exerted by molecular motors. We showed that actin transport by growing microtubule plus-ends results in much lower forces (0.10 pN) than are measured for microtubule motor proteins (1 pN to 10 pN) [39,40]. In direct competition, motor forces would therefore likely dominate over the condensation forces.…”
Section: Discussionmentioning
confidence: 72%
“…Actin transport by growing microtubule plus ends results in much lower forces than are measured for microtubule motor proteins 0.10 pN for microtubule growth compared to 1-10 pN for single motors or collectives of motor proteins) [33, 34]. In direct competition, motor forces would therefore likely dominate over the condensation forces.…”
Section: Discussionmentioning
confidence: 99%
“…Optical traps and in vitro motility experiments have been used to study how force and motion generation change with increasing numbers, N, of motors (9)(10)(11) and in general show that the mechanics of many motors working together is not a simple sum of the molecular mechanics of individual motors (4,12,13). Consistent with the chemical thermodynamic model that we first proposed over 20 years ago (14), many studies now indicate that force is collectivelygenerated and thermally-distributed within systems of motors (12,13,15). This leads to emergent mechanochemical properties (12,13,16) that are more accurately described by the thermodynamics of a motor ensemble than by molecular mechanics (14,17,18).…”
Section: Introductionmentioning
confidence: 80%
“…A natural extension to our work would be to include force dependence in the unbinding rate k off as has been done in [ 1 , 14 , 51 ] and recently by Ucar & Lipowsky [ 71 ]. We would expect that including this effect would increase the force sensitivity, increase the time taken to reach steady state, decrease the stall force and decrease the mean velocity due to the zipper effect of successive leading motors experiencing the force-dependent unbinding.…”
Section: Discussionmentioning
confidence: 99%